(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
This article relates to the epigraphic documents concerning the cult of Hygieia. The research focuses on the typology of the inscriptions of Epidauros, place where the most important Asklepios’s shrine stands, whose cult spread all over the Greek world; Hygieia was associated to Asklepios’s cult. The epigraphic sources of Hygieia’s cult in Attica are very important as here, besides Asklepios, it is associated to other healers such as Aminos, Amphiaraos, Telesphoros. On the other hand in Crete, although there were many Asklepieia, the cult of Hygieia has very few epigraphic testimonies in Lebena and Lissos, but these inscriptions are very interesting because of the use of Goddess Hygieia’s epithet of Synodoiporos besides the more common name of Soteira.